A RESOURCE-BASED VIEW (RBV) OF PRODUCT DEVELOPMENT: CASE STUDY OF PT. LANGGENG MAKMUR INDUSTRI, TBK. - Khalisa Balqis; Shelly Eka Agustina; Popy Rufaidah (AIBPM Publisher, 2018)
This study aims to discuss the implementation of Resource-Based View (RBV) modelin product development. This model is used as a basis to explore the application of four types of capabilities as a strategic source in product development based on process efficiency and product effectiveness.The research method uses case study that aims to reveal information factually, structured, and accurately about the object under study.The results show that RBV model approach to product development can be used by the company.This study shows the applied managerial implications of the RBV model in terms of (1) technological capability, only applies R&D and manufacturing in the process of innovation. If the company is determined to achieve the process efficiency, it needs to focus more on technology capability design and technological complementary. (2) In external integrative capability, the company only implements managerial process and managerial system, (3) in internal integrative capability, the company only applies managerial process and managerial system. If the company is determined to achieve product effectiveness, the company needs to focus more on external integrative capabilities in the form of absorptive structures and cultures and values for external absorption and internal integrative capabilities in the form of integrative structures and cultures and values for internal absorption. (4) In marketing capabilities, the company has implemented strategic marketing management. If the company is determined to produce product effectiveness, it should focus more on marketing capabilities in the form of market research tools, marketing-mix policies, and marketing complementary. Keywords: resource-based view model, product development